1999
DOI: 10.3109/08860229909066966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Metabolic Acidosis on Renal Growth and Renal Sodium Handling in Uninephrectomized Rats

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In this regard, we have previously shown that chronic metabolic acidosis, caused by NH 4 Cl feeding, leads to nephron hypertrophy and to a decreased watersalt reabsorption by the kidneys [1,25,26]. Since renal ion tubule transport is highly dependent on mitochondrial energy and because mitochondria have been implicated in a variety of metabolic disorders, we examined mitochondrial energy-linked functions in chronic metabolic acidotic rats.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, we have previously shown that chronic metabolic acidosis, caused by NH 4 Cl feeding, leads to nephron hypertrophy and to a decreased watersalt reabsorption by the kidneys [1,25,26]. Since renal ion tubule transport is highly dependent on mitochondrial energy and because mitochondria have been implicated in a variety of metabolic disorders, we examined mitochondrial energy-linked functions in chronic metabolic acidotic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Fractional sodium (FENa + ) and potassium (FEK + ) excretions were calculated as CNa + / CCr and CK + /CCr, respectively, where CNa + and CK + are the ion clearances and CCr is the creatinine clearance. The fractional proximal (FEPNa + ) and post-proximal (FEPPNa + ) sodium excretions were calculated as CLi + / CCr x 100 and CNa + /CLI + x 100, respectively (18,19). Changes in fractional excretion were estimated using the values from sham-operated rats.…”
Section: Statistics and Calculationsmentioning
confidence: 99%
“…39 Rarely liver disease can result in prerenal azotemia with an elevated FeNa because of sodium bicarbonate wasting from alkalosis 30 or alternatively because of loss of urea production that is necessary for water reabsorption and urine concentration. 101 Similarly bicarbonate conservation in acute (but not chronic) respiratory acidosis may cause a false depression through sodium bicarbonate conservation and generation 31 while metabolic acidosis has also been associated with an elevated FeNa regardless of volume 32,33 perhaps through hypercalcemia and hypomagnesemia may also interfere with tubular ability to conserve sodium even in the presence of hypovolemia. 40 Extremes of age both young and old can affect both sodium excretion.…”
Section: Ureamentioning
confidence: 99%
“…Similarly, chronic (but not acute) respiratory acidosis is associated with a decrease in FeNa because of sodium bicarbonate generation and conservation by the tubules. 32 Chronic metabolic acidosis may also result in sodium wasting, 33,34 presumably because of a different mechanism where acidosis may disrupt active transport. Surprisingly, while use of diuretics are well known to make the FeNa unreliable, [36][37][38][39] other drugs, such as amphotericin, that are known to cause proximal tubular damage may not.…”
Section: Fenamentioning
confidence: 99%
See 1 more Smart Citation